PENERAPAN PENDEKATAN KONTEKSTUAL BERBASIS ETNOGRAFI MAJALAYA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT - Hardiani, Dini; Irawati, Riana; Maulana, M. (Jurnal Pena Ilmiah, 2017)
This research is part of research report of Contextual Approach Based on Majalaya Ethnography to improve mathematical problem solving ability. This research is a quasi-experimental research with non-equivalent control research design. The population in this research is all elementary school students in Majalaya sub-district of Bandung Regency, while the sample is the fourth grade students of SDN Majasetra 02 and SDN Babakan Lapang that is decided by using quota sampling and purposive sampling. After that all fourth grade students in both elementary schools were given basic ability test to know the equality of ability between the two elementary schools. Based on the results of data analysis, it can be concluded that the improvement of students' mathematical problem solving ability that is acquired through learning with the contextual approach based on Majalaya ethnography and the conventional learning does not show significant differences, but the contextual learning process based on Majalaya ethnography is better than conventional approach.